The Agnipath Scheme of the Government of India: A Dilemma for Nepal - Adhikari, Khaga Nath (NCWA Annual Journal, 2024)
The Agnipath Scheme was unveiled by the Government of India on June 14, 2022. It plans to recruit Agniveers for a period of four years, after which only 25 percent would be retained in the service, and the rest would be demobilized with an amount of INR 1.17 million. The laid-off Agniveers will not be entitled to pension and other benefits provided for defence pensioners. This plan mainly aims at lowering the average age of the Indian military and reducing defence expenditure. The introduction of the new scheme has put Nepal into a dilemma as to whether or not to allow its citizens to join the Indian Army as provisioned by the 1947 Tripartite Agreement. This is a complex issue and needs to be analyzed from economic, social, political, and diplomatic and security perspectives before making a decision. There are pros and cons on either side. Therefore, a dispassionate and pragmatic decision needs to be taken following in-depth discussions and analyses.